2005
DOI: 10.1152/japplphysiol.00331.2005
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein cross-sectional area and flow and orthostatic tolerance: a 90-day bed rest study.

Abstract: The objective of this study was to evaluate the changes in the portal vein cross-sectional area (PV CSA) and flow during a stand test associated with orthostatic intolerance. Eighteen subjects underwent a 90-day head-down tilt (HDT) bed rest at 6 degrees: 9 controls (Con) and 9 with flywheel exercise countermeasures (CM). At post-HDT, nine subjects (5 CM, 4 Con) were tolerant, and nine were intolerant. The PV CSA was measured by echography. We found that at HDT day 85, the PV CSA at rest had increased less in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
(47 reference statements)
2
28
0
Order By: Relevance
“…This suggests that the femoral flow was reduced more than cerebral flow and that the regulating systems (baro-reflexes, cerebral auto-regulation, local leg and splanchnic vasoconstriction) were still operational in this group even after long-term HDBR. This was also observed during supine LBNP or stand tests after long duration HDBR (Arbeille et al 2005(Arbeille et al , 2008b.…”
Section: Discussionsupporting
confidence: 55%
“…This suggests that the femoral flow was reduced more than cerebral flow and that the regulating systems (baro-reflexes, cerebral auto-regulation, local leg and splanchnic vasoconstriction) were still operational in this group even after long-term HDBR. This was also observed during supine LBNP or stand tests after long duration HDBR (Arbeille et al 2005(Arbeille et al , 2008b.…”
Section: Discussionsupporting
confidence: 55%
“…Results from multiple human spaceflight [7] and bed rest studies [1,2,9] have demonstrated the adaptational changes of the arterial vasculature in both real and simulated microgravity, which could possibly contribute to postflight orthostatic intolerance. Animal studies applying mice experiencing real spaceflight [28] and tailsuspended hindlimb unweighting (HU) rats [10,18,24,34,35] also give support to the involvement of microgravity-induced vascular responsiveness adaptations in postflight orthostatic intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Splanchnic hyperemia occurs in real or simulated microgravity (bedrest in man, hindlimb suspension in rats) where it is associated with orthostatic intolerance, adrenergic hyporeactivity 41;42 , and enhanced microvascular production of NO through increased transcription of NOS isoforms 43;44 . Increased NO has been reported in both postural tachycardia syndrome and VVS 45–47 but those results are controversial due to measurement methods and lack of subsetting 46 .…”
Section: Discussionmentioning
confidence: 99%